KONFLIK SOSIALXDALAMXNOVELXTARIANXBUMIXKARYA OKAXRUSMINI:XKAJIANXSOSIOLOGIXSASTRA - Skolastika Juita; Eko Cahyo Prawoto (Buana Bastra, 2020)
This research aims to for knows describe and explain (1) Self-conflict in Oka Rusmini's Earth ance Novel (2) Inter-Individual Conflict in Oka Rusmini's Earth Dance Novel (3) Positive Function of Conflict in Oka Rusmini's Earth Dance Novel. This research uses a literature sociology study. The approach used in this research is descriptivexqualitativexresearch. Thexdataxinxthisxstudyxarexinxthexform ofxwords, sentences in the form of expressions, and dialogues between characters that show self-conflict and between individuals and the positive function of conflict which is the focus of the research. Thexdataxsourcexinxthisxstudyxis the novel Tarian Bumi by Oka Rusmini.xDataxcollectiox techniquesxinxthisxstudy used the observation and note technique. The results of this study are able to explain which include self-conflict, between individuals and the positive function of conflict that occurs in Balinese society. Through the novel Tarian Bumi by Oka Rusmini, it explains the struggle of women and the conflicting rules that exist in the family which makes one of the main characters, Ida Ayu Telaga Pidada, willing to leave her national title. Telaga's rejection of the mother caused the relationship between mother and child to break up.